2010
DOI: 10.1016/j.nlm.2010.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Role of beta-adrenergic receptors in the ventromedial prefrontal cortex during contextual fear extinction in rats

Abstract: It has been reported that stress-related activation of the noradrenergic system strengthens the formation of aversive memories and that beta-adrenergic receptors seem to be involved in this emotional memory processing. In this study, the effects of beta-adrenergic compounds on the extinction of contextual conditioned fear responses were evaluated. Rats were trained with footshock in a conditioning box. In the 3 days following the training, the animals were re-exposed to the apparatus and received either a sing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 70 publications
2
29
0
1
Order By: Relevance
“…In agreement with our result, our previous study demonstrated that atenolol decreased memory retrieval [29]. The propranolol injection into the ventromedial prefrontal cortex impaired the acquisition and the consolidation of extinction in rats [30]. Moreover, injections of β 1 -AR antagonists into the amygdala produced memory impairment [21,31].…”
Section: Discussionsupporting
confidence: 91%
“…In agreement with our result, our previous study demonstrated that atenolol decreased memory retrieval [29]. The propranolol injection into the ventromedial prefrontal cortex impaired the acquisition and the consolidation of extinction in rats [30]. Moreover, injections of β 1 -AR antagonists into the amygdala produced memory impairment [21,31].…”
Section: Discussionsupporting
confidence: 91%
“…Propranolol has been studied extensively, but with mixed results, leading many to believe it is an ineffective therapeutic option (Raskind et al, 2003; Strawn & Geracioti, 2008; Tawa & Murphy, 2013). In addition, many studies in rodents have shown that systemic propranolol prior to delayed extinction impairs long-term retention (Cain et al, 2004; Do-Monte et al, 2010; Fitzgerald et al, 2015). One possibility is that, similar to extinction learning itself, the efficacy of propranolol as a fear-reducing agent is sensitive to the timing of administration.…”
Section: Does Propranolol Enhance Extinction Learning and Augment mentioning
confidence: 99%
“…Nonetheless, pharmacotherapies that either dampen NE transmission, such as the α1-adrenoceptor antagonist prazosin, the α2 agonist clonidine, and the non-selective β antagonist propranolol, or enhance NE transmission such as the α2 antagonist yohimbine, have shown some success in diminishing the exaggerated fear responding associated with PTSD (Belkin & Schwartz, 2015; Morris & Bouton, 2007; Powers, Smits, Otto, Sanders, & Emmelkamp, 2009; Raskind et al, 2003; Strawn & Geracioti, 2008; Tawa & Murphy, 2013; Taylor, Freeman, & Cates, 2008; Wangelin, Powers, Smits, & Tuerk, 2013). Yohimbine, as well as the non-selective β agonist isoproterenol, can enhance extinction learning (Cain, Blouin, & Barad, 2004; Do-Monte et al, 2010; Morris & Bouton, 2007; Powers et al, 2009), as well as memory consolidation or reconsolidation (Dębiec, Bush, & LeDoux, 2011; Gazarini, Stern, Carobrez, & Bertoglio, 2013). For these reasons, there has been a resurgence of interest in using noradrenergic drugs as adjuncts to cognitive-behavioral therapies for PTSD.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it is well accepted that norepinephrine facilitates, rather than impedes, memory formation through b-receptor activation (McGaugh, 2000). Finally, research has demonstrated that propranolol impairs extinction learning (for review see Mueller and Cahill, 2010) in both aversive (Do-Monte et al, 2010;Merlo and Izquierdo, 1967;Mueller et al, 2008;Ouyang and Thomas, 2005) and appetitive paradigms (LaLumiere et al, 2010).…”
Section: Time In Chamber (Sec)mentioning
confidence: 99%